Spatio-temporal Analysis of Unemployment Rate in Poland; Przestrzenno-czasowa analiza stopy bezrobocia w Polsce - Karolina Lewandowska-Gwarda (Comparative Economic Research. Central and Eastern Europe, 2012)
The aim of this paper is to present results of spatio-temporal analysis of unemployment rate in Poland, with the usage of advanced spatial econometric methods. The analysis was done on data collected for 'powiat' level between 2006 and 2010. GlS and ESDA tools were applied for visualization of the spatiotemporal data and identification of spatial interactions between polish counties on labor market. Multi-equation spatial econometric models were used to describe unemployment rate in relation to selected social-economic variables. – – Celem opracowania jest przestrzenno-czasowa analiza poziomu stopy bezrobocia w Polsce, z wykorzystaniem zaawansowanych metod ekonometrii przestrzennej. Badanie przeprowadzono na danych statystycznych zebranych na poziomie powiatu, w latach 2006-2010. Narzedzia GIS i ESDA zostały wykorzystane w celu wizualizacji zmiennych oraz identyfikacji interakcji przestrzennych zachodzacych pomiedzy badanymi jednostkami terytorialnymi na rynku pracy. Wieloroẃnaniowe modele o roẃnaniach pozornie niezalezṅych zastosowano do opisu wpływu wybranych zmiennych makroekonomicznych na kształtowanie sie poziomu stopy bezrobocia w Polsce w badanym okresie.
Keywords: 330